Transforming Conventional Construction Binders and Grouts into High-Performance Nanocarbon Binders and Grouts for Todays Constructions - Katman H.Y.B.; Khai W.J.; K?rg?z M.S.; Nehdi M.L.; Benjeddou O.; Thomas B.S.; Papatzani S.; Rambhad K.; Kumbhalkar M.A.; Karimipour A. (MDPI, 2023)
The transformation of conventional binder and grout into high-performance nanocarbon binder and grout was evaluated in this investigation. The high-performance nanocarbon grout consisted of grey cement, white cement, lime, gypsum, sand, water, and graphite nanoplatelet (GNP), while conventional mortar is prepared with water, binder, and fine aggregate. The investigated properties included unconfined compressive strength (UCS), bending strength, ultrasound pulse analysis (UPA), and Schmidt surface hardness. The results indicated that the inclusion of nanocarbon led to an increase in the initial and long-term strengths by 14% and 23%, respectively. The same trend was observed in the nanocarbon binder mortars with white cement, lime, and gypsum in terms of the UCS, bending strength, UPA, and Schmidt surface hardness. The incorporation of nanocarbon into ordinary cement produced a high-performance nanocarbon binder mortar, which increased the strength to 42.5 N, in comparison to the 32.5 N of the ordinary cement, at 28 days. 2022 by the authors.